On the identity of Lepismium lineare and L. warmingianum (Cactaceae, Rhipsalidae) - Lombardi, Julio Antonio [UNESP] (Magnolia Press, 2014)
Field surveys, cultivation tests and literature examination allowed to clarify the identity and morphological distinction of Lepismium lineare and L. warmingianum. A diagnostic key for the Lepismium species in Brazil is also provided. © 2014 Magnolia Press.
Keywords: Cactaceae; Lepismium lineare; Lepismium warmingianum; Taxonomy